Prevalence of tuberculosis with multiple and extensive drug resistance according to the data of Federal register of tb cases - V. V. Testov; I. A. Vasilyeva; S. A. Sterlikov; I. D. Medvinskiy; K. A. Glebov; E. G. Аntonova; E. D. Filina; I. A. Sidorova (Туберкулез и болезни лёгких)
.